Spatial Equity in Devolved Healthcare: Is It Quality or Quantity Causing Spatial Clustering in Maternal Health Utilization when Affordability has been Addressed? - Nyangueso, Samuel Ouma; Hayombe, Patrick Odhiambo; Owino, Fredrick Omondi (Published by Scientific & Academic Publishing, 2018)
Devolved healthcare in Kenya, from onset, apparently concentrated on increasing, expanding, upgrading and refurbishment of health facilities as well as improving staff base among other interventions in a bid to decentralize health services closer to people. However, proximity and availability are seldom the reasons for patient provider choices and effective healthcare provisions. It isn’t uncommon for maternal patients to flock certain localities for healthcare irrespective of distance, especially in an environment where patients have freedom to choose providers and in the era of free maternity. The paper sought to spatially explore major cause of local spatial clustering for maternal health utilization within lowest decentralized units in Kenya. Applying multiple-case design, the study focused on County of Siaya and 30 Wards therein, as clusters for hotspot analysis of Antenatal Care and Skilled Birth Attendance before and after devolution in Kenya. Targeted descriptive analysis involving hot spot and cold spot Wards was done to provide qualitative explanations to the spatial analysis results. Retrospective patient-based surveys from Kenya’s Health Information System (DHIS 2), geolocation of health facilities from Kenya Master Health Facility List (KMHFL) and reviews of relevant literature supplied the requisite data by each registered health facility and by each Ward in Siaya County. Getis Ord Gi* hot spot analysis, using ArcGIS 10.3, revealed existence, persistence and intensifying spatial clustering of maternal healthcare utilization after devolution. Presence of established public referral health facility was largely responsible for the hot spots in maternal health services utilization, but not facility-to-population ratio as some facilities recorded zero maternal service offered. This implies that quality overrides quantity, and proximity, in patient choices of providers resulting into spatial clustering in utilization within respective decentralized units. Whereas increasing health facilities is well intentioned, their service utilization, quality and comprehensiveness are paramount in achieving spatial equity in devolved healthcare, especially in Kenya.
Keywords: Spatial equity; Quantity and quality of devolved healthcare; Spatial clustering